Oxaliplatin-Induced Lhermitte's Sign in Gastric Cancer - Okamoto, Takeshi (Case Rep Oncol Med, 2020)
A 64-year-old Japanese man with no significant medical history presented with epigastric discomfort of 2-weeks' duration. He was diagnosed with metastatic HER2-positive gastric cancer. Chemotherapy with capecitabine, oxaliplatin, and trastuzumab was initiated. During the eighth cycle, he suddenly complained of electric shock-like pain in both legs upon neck flexion, consistent with Lhermitte's sign. Oxaliplatin was discontinued, and Lhermitte's sign resolved after 3 months. Neurotoxicity is commonly observed in platinum-based chemotherapy, but Lhermitte's sign is rare. This is the first report of oxaliplatin-induced Lhermitte's sign in a gastric cancer patient.